Muros et portas Cicero fecit : Boundaries and movement in the urban borderscape of ancient Roman Ostia - Järvinen, Niko (My University, 2025)
New city walls were built in ancient Roman Ostia by the mid-1st century BCE, enclosing the urban space that had expanded remarkably beyond the original colony that was founded three centuries earlier at the mouth of the river Tiber. These walls originated the new urban borderscape that delimited and defined the city until the decline of Roman urbanity in Ostia. The city walls were later augmented by another defensive wall that was built around the extended urban area of the city north of the river, in the Trastevere Ostiense. In addition to the city walls, the urban borderscape consisted of many other features, such as natural, magico-religious, hygienic, and economic boundaries, thereby altogether separating what was considered to be urban from suburban and non-urban. In this study, these boundary features and their biographic development over time is examined. This is furthered with another biographical analysis of the movement that flew through these boundaries. Examination of these phenomena is executed by synthesising all the knowledge on these topics from archaeological data and secondary research. The aim of this analysis is to understand how the urban space of Ostia was defined and perceived, and how it thus participated to the formulation of the urban identity of the Ostians. The spatial and movement studies from the previous decades serve as the theoretical principles of the study in an attempt to make a leap from the material evidence to the interpretation of social and mental features of the ancient Roman society of Ostia.
Keywords: Ostia, ancient Rome, Roman archaeology, Roman Empire, urban studies, spatial studies, space, urban border, borderscape, movement, city walls, urban identity